Efficacy and safety of topical JTE‐052, a Janus kinase inhibitor, in Japanese adult patients with moderate‐to‐severe atopic dermatitis: a phase II, multicentre, randomized, vehicle‐controlled clinical study. (15th January 2018) - Nakagawa, H.; Nemoto, O.; Igarashi, A.; Nagata, T.
Summary: Background : JTE‐052 is a novel Janus kinase inhibitor presently under clinical development for the topical treatment of atopic dermatitis (AD). Objectives : To evaluate the efficacy and safety of JTE‐052 ointment in Japanese adult patients with AD. Methods : Patients with moderate‐to‐severe AD were randomized (2: 2: 2: 2: 1: 1) to receive JTE‐052 ointment at 0·25%, 0·5%, 1% or 3%, the vehicle ointment or tacrolimus 0·1% ointment (reference) twice daily for 4 weeks. The primary efficacy end point was the percentage change in modified Eczema Area Severity Index (mEASI) score from baseline at the end of treatment (EOT). Secondary efficacy end points included change from baseline in the pruritus numerical rating scale (NRS) score. Results : In total, 327 patients were enrolled. At EOT, the least‐squares mean percentage changes from baseline in mEASI score for JTE‐052 at 0·25%, 0·5%, 1% and 3% and the vehicle ointment were −41·7%, −57·1%, −54·9%, −72·9% and −12·2%, respectively. All JTE‐052 groups showed significant reductions of mEASI score vs. the vehicle group ( P < 0·001 for all). In the tacrolimus group, the mean percentage change in mEASI score was −62·0%. The JTE‐052 groups also showed significant improvement in other parameters; notably, the pruritus NRS score was reduced as early as day 1 night‐time. JTE‐052 ointment at doses up to 3% was safe and well tolerated. Conclusions : Topical JTE‐052 markedly and rapidly improved clinical signs and symptoms in Japanese adult patients with moderate‐to‐severe AD, with a favourable safety profile. The study results indicate that topical JTE‐052 is a promising therapeutic option for AD. The trial registration number is JapicCTI‐152887. Abstract : What's already known about this topic? Atopic dermatitis (AD) is a chronic inflammatory skin disease with impaired skin barrier function and pruritus. The results of some clinical and experimental studies support the concept that inhibition of cytokine signalling via Janus kinase (JAK) may contribute to the improvement of AD. What does this study add? Topical JTE‐052, a novel JAK inhibitor, markedly and rapidly improved clinical signs and symptoms in Japanese adult patients with moderate‐to‐severe AD and showed a favourable safety profile. The study results indicate that topical JTE‐052 is a promising therapeutic option for AD. Linked Comment:  Bissonnette. Br J Dermatol 2018;178 :321 . Plain language summary available online Respond to this article